(untitled) (The Planet, 2023)
Background: Common in clinical practice is a skindisorder known as seborrheic dermatitis (SD). There areseveral different names for this disorder, which illustratesits complexity: sebopsoriasis, seborrheic dermatitis,seborrheic eczema, dandruff, and pityriasis capitis. Thepathogenesis of SD is still highly debated despite thedisease’s prevalence. Objective: The primary objective ofthis research was to evaluate the prevalence of andexposure to risk factors for seborrheic dermatitis inBangladesh. Methods: A total of 300 patients wereincluded in the cross-sectional study that was carried outat the 250-bed general hospital in Jamalpur, Bangladesh.The research was carried out between January 2020 andDecember 2021. Results: In our investigation, maximumpatients (21.3%) were between 20 to 29 years of agegroup. Minimum number of patients (5.7%) were below 20 years of age group. 62%patients were male and 38% patients were female. Among them (40%) are child and (60%)are adult.Maximum patients involved sites (60%) of seborrheic dermatitis were scalp. 20%patients had seborrheic dermatitis in anterior hairline.15% had seborrheic dermatitis incentral chest. And only 5% patients had dermatitis on other sites (eyebrows,genitalregion,glabella region of forehead,ears,nasal alar creases).Maximum munber of patientshad concurrernt acne(30%) and minimum number of patients (8%) had folliculitis in ourstudy. Conclusion: SD patients have different clinical features depending on their age, sex or medical history, which can lead to severity changes or scalp involvement in the clinicalsetting.